2000
DOI: 10.1007/s11663-000-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

A new criterion for internal crack formation in continuously cast steels

Abstract: To estimate the cracking condition in continuously cast steels, a new model for critical fracture stress given from the measured critical strain has been proposed, which can take into account the brittle temperature range and strain rate. The effects of brittle temperature range and strain rate on critical strain for internal crack formation were analyzed. When the brittle temperature range and strain rate were increased, the possibility of internal crack formation increased due to the decreasing critical stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
161
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 37 publications
(24 reference statements)
1
161
0
2
Order By: Relevance
“…[20][21][22][23][24] Recently, authors take into account the brittle temperature range and strain rate to predict the critical strain as follows. 19) . (1) where j is the constant, m* is the strain rate exponent on the critical strain and n* is the brittle temperature range exponent on the critical strain.…”
Section: Critical Strain and Critical Fracture Stress Formentioning
confidence: 99%
See 4 more Smart Citations
“…[20][21][22][23][24] Recently, authors take into account the brittle temperature range and strain rate to predict the critical strain as follows. 19) . (1) where j is the constant, m* is the strain rate exponent on the critical strain and n* is the brittle temperature range exponent on the critical strain.…”
Section: Critical Strain and Critical Fracture Stress Formentioning
confidence: 99%
“…Many investigations 11,19,26) on the relationship between the crack index by the industrial observations and the carbon content have reported carbon content of maximum cracking as the carbon range between 0.08 wt% C and 0.25 wt% C. Thus, the cracking prediction from critical strain or critical fracture stress has to show possibility below 0.08 wt% C and above 0.25 wt% C steels. But, Won et al 19) pointed out that the cracking prediction based on critical stain or critical fracture stress can not explain the cracking phenomenon of whole carbon range, even though the calculated critical strain and critical fracture stress are in good agreement with the experimentally measured data.…”
Section: (4)mentioning
confidence: 99%
See 3 more Smart Citations